Cross Cultural Workers for women and families from migrant and refugee backgrounds: a mixed-methods study of service providers perceptions - Helen J. Rogers; Lily Hogan; Dominiek Coates; Caroline S. E. Homer; Amanda Henry (BMC, 2021)
Abstract Background Women from migrant and refugee backgrounds who live in high-income countries are at increased risk of adverse perinatal outcomes, including mental health issues, preterm birth and maternal and infant mortality. There is a need to implement and evaluate models of care to meet their specific needs in order to improve health outcomes, their experiences of care, and overcome barriers to access. In Sydney, Australia, a unique model of care was implemented to support women and families from migrant and refugee backgrounds to access health and community-based services through the continuum of pregnancy to the early parenting period. This model of care is known as the Cross Cultural Workers (CCWs) in Maternity and Child and Family Health Service (the CCW Service). The aim of this study was to explore the perceptions of service providers regarding the CCW Service and identify recommendations for improvement. Methods A mixed-methods study was conducted consisting of surveys and face to face semi-structured interviews. Service providers were recruited from hospital-based maternity and community-based services. Survey data were analysed descriptively. Interviews were analysed using qualitative content analysis. Results Sixty-nine service providers completed surveys and 19 were interviewed. The CCW Service was highly regarded by service providers who perceived it to be critical in improving care for women from migrant and refugee backgrounds. The overarching theme from the interviews was the ability of the CCW Service to act as a 'bridge to health' through the provision of culturally responsive care. There were three main categories; supporting access to health and community-based services, improving the healthcare experience, and organisational factors, including part-time hours, capacity, heavy workloads and confusion/lack of clarity regarding the CCW role, which affected CCWs' capacity to optimally support service providers in providing culturally responsive care. These limitations meant CCWs were not able to meet demand, and fully operationalise the model. Conclusion Service providers perceived the CCW model to be a culturally responsive model of care tailored to the needs of women and families from migrant and refugee backgrounds, that reduces barriers to access, and has the potential to improve perinatal outcomes, and women's experience and satisfaction with care.